The Typology of Lived Experience of Love - Hakimeh Malekahmadi; Asghar Mirfardi; Maryam Mokhtari (پژوهش‌های راهبردی مسائل اجتماعی ایران, 2019)
Introduction Love is one of the most important human concepts and is the basis of the formation of the relationship between the two sexes, which has been studied by various scholars in various ways. There has been little agreement on the nature of love. Love is influenced by different social conditions and the type of dominant lifestyle of each era defines its nature. In addition, love is an event, that most people have experienced at least once in their lives. However, every experience from the perspective of the actors is a unique experience. Therefore, love is a multifaceted phenomenon, that, on the one hand, is related to the deepest individual emotions and particular personality traits as well as psychological and subconscious traits and, on the other hand, is influenced by social conditions and structures.   Material & Methods This study is a phenomenological study. Phenomenology examines the experiences of subjects. Researchers in the present study, studied the participants' experiences of ‘love’. The concept of love in this study, is the title of an experienced, attainable and earthly issue. The purpose of the present study was to explore the experience of living of love and its typology. For this purpose, by the in-depth phenomenological approach, 14 students at the University of Isfahan and Isfahan University of Technology, who had experienced ‘love’, were interviewed in depth. Findings were analyzed using Gollizzi method.   Discussion of Results & Conclusions    Analyzing the interviews indicated that four types of love can be deduced from the participants' experience. The first type of typology was ‘love as an achievement' with two sub-categories of  build shared experiences and climbing. The meaning of love as an achievement is a relationship that can turn into components of love. The central idea in this way is that the parties themselves, must make love. In this view, love is formed by mutual effort over time. So there is no belief in love at a glance. The second type of typology  was ‘love as an unexpected emotional experience’ with two sub-categories of achievable experience and unattainable experience. In this type of love, there is a relative belief in love at a glance and parties expect a perfect relationship. So, there is no attempt to build a relationship. Itseems  that part of this relationship have been assigned to ‘accident’, ‘chance’, and ‘fortune’. The Third type of typology was ‘love as an addiction’. In this way, falling in love is a form of addictive behavior. It is important to experience the excitement and to deal with abnormal acts. But, as soon as the initial emotions are over, the person loses interest in the lover. Not reaching the lover is one of the central ideas of this kind of love. The fourth type of typology was ‘love as a physiological experience’. In this way, the experience of love is more of a physiological and hormonal process. But, love as a hormonal process can be the basis for other forms of relationships. Generally, participants shape different kinds of love based on different experiences in life and structure in which they grew up.  But, they encounter love as something earthly and attainable, which is common among all of them. Another finding of the study was the extraction of a kind of non-romantic experience: ‘love-free sexual experience’. In this way, there is no belief in love, and love is just a beautiful cover to meet needs, especially sexual desires. After analyzing the findings, theories related to love were reviewed, although there are different theories about love in different fields, but the recent conceptual foundations of research are drawn from the theories of Alan Badio, Robert Stenberg, Sigmund Bowman, and Helen Fisher. For this purpose, after coding and extracting the categories, the theories in the field were studied, and those that somehow supported the findings and explained it more clearly were selected.